Longitudinal Change in Knee Cartilage Thickness and Function in Subjects with and without MRI-Diagnosed Cartilage Damage - Wisser, Anna; Lapper, Andreas; Roemer, Frank; Fuerst, David; Maschek, Susanne; Wirth, Wolfgang; Duda, Georg N.; Eckstein, Felix (Cartilage, 2020)
Objective. Cartilage damage diagnosed by magnetic resonance imaging (MRI) is highly prevalent in the population. In this article, we explore whether such cartilage damage is associated with greater longitudinal change in 3D cartilage thickness and knee function in subjects without (risk factors of) knee osteoarthritis. Design. Eighty-two knees of Osteoarthritis Initiative healthy reference cohort participants had baseline and 4-year follow-up MRI and knee function data. Baseline presence of semiquantitatively assessed MRI-based cartilage damage (MOAKS [MRI Osteoarthritis Knee Score] = grade 1.0) was recorded by an experienced radiologist. Longitudinal femorotibial cartilage thickness change was determined after segmentation, using location-independent methodology. Knee function was evaluated by patient-reported outcomes and functional performance measures. Statistical comparisons included analysis of covariance adjusting for age, sex, and body mass index. Results. Forty-five percent of the participants had cartilage damage in at least one femorotibial subregion; the cartilage thickness change score was 15% greater in participants with than in those without damage (1216 +/- 434 vs. 1058 +/- 277 mu m). This difference reached borderline statistical significance with and without adjustment for age, sex, and body mass index (P = 0.05). No significant differences in the change of patient-reported outcomes of knee function (PASE [physical activity score of the elderly] and WOMAC [Western Ontario McMaster Osteoarthritis Index]) or chair stand test results were detected. Of those without femorotibial damage, 58% had cartilage damage in at least one femoropatellar subregion; these had a 9% greater femorotibial cartilage change score than those without femoropatellar or femorotibial damage (difference not statistically significant). Conclusions. In the absence of osteoarthritis risk factors, semiquantitatively assessed MRI-based cartilage damage appears to be associated with greater longitudinal location-independent femorotibial cartilage thickness changes, but not with greater functional deteriorations.
CRIS-Team WoS Importer:2021-02-05